Réponses

2013-04-04T20:09:46+02:00

E = /3 - 2 * /27 + 4 * /300

E = /3 - 2 * /3*9 + 4 * /3*100          27=3*9 et 300=3*100

E = /3 - 2 * /3 * /9 + 4 * /3 * /100    on sépare : /3*9=/3*/9 et /3*10=/3*/10

E = /3 - 2 * /3 * 3 + 4 * /3 * 10         /9=3 et /100=10 (3²=9 et 10²=100)

E = /3 - 2 * 3 * /3 + 4 * 10 * /3        on met dans l'ordre

E = /3 - 6 * /3 + 40 * /3                    on calcule

E = /3 - 6/3 + 40/3                           on calcule

E = 35/3                                            aide : remplace /3 par x : x - 6x + 40x = 35x

 

J'espere qe t aura compri sinon esite pa a me redemmander !